Інтенсифікація життєвих процесів у рослин в умовах культури як результат їх адаптації до нових чинників середовища - Bulakh, P.E. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
The concept of "vitality of plants" is seen as a characteristic intensity manifestation process of growth and development, reproduction, resistance to extreme conditions and diseases. The example introduced herbaceous perennials and shrubs proved that a culture is the intensification of basic life process. This is reflected in the increase of the overall size of the plants and their vegetative and generative organs downward trend apical dominance, resulting in the acceleration of foundation and formation of axillary and adventitious buds. There also enhance branching shoots of cultivated plants, a significant reduction in age-specific life stages and individuals. Examples intensification of vital process in terms of culture and generative sphere of plants which are shown to increase seed productivity and vivipariy phenomenon. It is shown that the intensification of various aspects of life organisms always reflected in their energy potential. Whereas energy principles optimal functioning of organisms and understanding of the volatile nature of plant resistance, formulated the important provision: indicators of energy homeostasis, adequately describing his condition, can be used as a criterion for its sustainability (criterion optimal functioning), the best in these conditions the state is responsible at least this indicator. The heating value of the plants specified colorimetric method is considered as integral assessment of the stability and performance of plants at different levels of organization of living matter. Presented and analyzed in this context quantitative data power consumption of plants collected in nature and circumstances of culture.